Wasps venoms of the genus Parachartergus sp. and Polybia sp (Vespidae: Polistinae) in Costa Rica: a biological potential to explore - Rodríguez-Picado, Ivonne (2022)
Latin America is home to a great diversity of species of Hymenoptera order, which comprises wasps of the genera Polybia and Parachartergus. Wasp stings characterize for causing reactions such as vascular permeability, activation and mobilization of inflammatory cells and inflammation mediating molecules. This has increased the biotechnological interest in wasp venom, in order to identify its bioactive components involved in biological responses, looking for molecules with specific activities. In recent decades, it has been found that the most promising wasps molecules are mastoparan peptides and other anticancer peptides (ACPs). The potential of these peptides attributes mainly to their size and amphipathic structure, which allows them to interact differently with cell membranes. The proteomic profile reported for the Polybia paulista venom motivates to study the profiles from different insects in Costa Rica, considering that the components of the venom may vary among different geographical areas, as well as between species and genera depending, for example, on their predators and prey. This document aims to highlight the pharmacological potential contained in the venom of wasps of the genera Parachartergus sp. and Polybia sp., mainly to treat cancer, taking advantage of Costa Rica’s biodiversity and technological capabilities, thereby contributing to the fight against one of the major causes of morbidity and mortality worldwide. The proteomic profile reported for the Polybia paulista venom motivates to study the profiles from different insects in Costa Rica, considering that the components of the venom may vary among different geographical areas, as well as between species and genera depending, for example, on their predators and prey. This document aims to highlight the pharmacological potential contained in the venom of wasps of the genera Parachartergus sp. and Polybia sp., mainly to treat cancer, taking advantage of Costa Rica's biodiversity and technological capabilities, thereby contributing to the fight against one of the major causes of morbidity and mortality worldwide.